Analisis Dampak Implementasi AI Dalam Proses Pengambilan Keputusan Manajerial Terhadap Etika Bisnis dan Keberlanjutan Organisasi: A Systematic Literature Review - Mutahira Nur Insirat; Hasri Ainun Syahfir; Asri Usman; Mediaty Mediaty (Politeknik Ganesha Medan, 2025)
This study systematically examines the impact of artificial intelligence (AI) implementation on managerial decision-making and its implications for business ethics and organizational sustainability. Using a Systematic Literature Review (SLR) methodology, this study identifies key trends from studies published between 2021 and 2024. Key findings suggest that AI implementation has the potential to improve operational efficiency and innovation but also brings significant ethical challenges, particularly related to algorithmic bias and lack of transparency. Ethical awareness among managers plays a crucial role in ensuring the fair and responsible use of AI. This study highlights the importance of integrating ethical considerations into AI implementation strategies to support organizational sustainability. In conclusion, while AI can accelerate the achievement of sustainability goals, its successful adoption is highly dependent on decision-makers' adequate understanding and application of ethics.